Төв Азийн уугуул оршин суугч угсаатнуудын түүхэн хөгжлийн динамикийн зарим асуудалд - М, Хурметхан (Journal of International Studies, 2008)
English title: Some dynamic issues of historical development of the Central Asian native ethno groups